Risk Factor and/or Prevalence of Tuberculosis in Nepal: A Systematic Literature Review - Pandey, Mukta Bhattarai; Koirala, Mamata Bhattarai (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2023)
Objective: The objective of this review was to synthesise evidence regarding the risk factor and/or prevalence of Tuberculosis in the Nepalese community. Method: A search strategy was used to identify the English language primary research studies published on or after 2018. Four databases namely, Cochrane, PubMed, ProQuest, and Web of Science were used to search data, and themes were identified to synthesise the data. Results: A sum of 1097 studies were recognised after the four database searches, excluding duplicates. Just four studies met the inclusion criteria after full article screening and were included for synthesis All the included studies showed evidence on prevalence of Tuberculosis. Three studies identified male gender as a risk factor for contracting Tuberculosis. Three studies showed the prevalence of Tuberculosis in health disorder context to be around or over 10%, only one study showed about four percent of prevalence of Tuberculosis in admitted patients Conclusions: Male genders possess a greater risk of contracting Tuberculosis in health disorder context , with the exception in Rifampicin-resistant Mycobacterium Tuberculosis(RR-MTB) which showed the opposite outcome. In terms of prevalence , majority of the sample exhibited around ten percent and over prevalence of Tuberculosis in health disorder context , apart from one study which showed around four percent prevalence of Tuberculosis in admitted patients. Therefore, further research is required to bridge these gaps. Moreover, there is a gap in the literature in terms of study location, population , and study design.